Portable armchair cane / Musa Razali … [et al.] - Razali, Musa; -, Adib Idham; -, Aishah Natasha; Md Juhari, Asyraf; -, Aiman Wafiy (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The Portable Armchair Cane represents a paradigm shift in mobility assistance, integrating innovative features into a traditional walking stick to enhance usability for individuals with disabilities. This versatile 2-in-1 device seamlessly transitions between a walking aid and a comfortable chair, offering unprecedented convenience for on-the-go users. With its compact design, integrated cup holder, and spacious pocket, the Portable Armchair Cane provides unparalleled support and accessibility, addressing the limitations of traditional mobility aids. By combining functionality with comfort, this groundbreaking solution promises to elevate the quality of life for individuals with disabilities, fostering independence and social inclusion. Currently in the design and prototyping phase, the Portable Armchair Cane holds immense potential to revolutionize mobility assistance and empower users to navigate their world with confidence and convenience.